If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -6(14 + -4x) = 32 5x + (14 * -6 + -4x * -6) = 32 5x + (-84 + 24x) = 32 Reorder the terms: -84 + 5x + 24x = 32 Combine like terms: 5x + 24x = 29x -84 + 29x = 32 Solving -84 + 29x = 32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '84' to each side of the equation. -84 + 84 + 29x = 32 + 84 Combine like terms: -84 + 84 = 0 0 + 29x = 32 + 84 29x = 32 + 84 Combine like terms: 32 + 84 = 116 29x = 116 Divide each side by '29'. x = 4 Simplifying x = 4
| y=x^2-2x+1 | | 2x+8=5x+77 | | 2x+8=5x | | 5x=-6x-9/3 | | (9n*n)=4+7n | | 2x-2y-2=0 | | Log(x)=1.3 | | logx=1.3 | | 2(x-1)=26.4 | | a^2+a-3a-3=0 | | ln(2x)=7 | | 2t^2-12t-25=0 | | -6+x=.6x-2.2+2 | | X+4=9+2x | | 35x-23=17 | | y=-5x+10 | | 0=6x+x^2+9 | | 7x-28=21 | | y=x+50 | | 3x+5=9x-(5-2x) | | x-(3x+1)=2x-(4x+3)-x | | 7p+12=13+6p | | 12-4x-x^2=36-16x^2+16 | | 2+10= | | -5.2x-3.3=22.7 | | 10y+2=7 | | 2*d=5d | | 4[-2(4x+3)+2(5x-5)]= | | 9y+(-3y-5)=4y-7 | | 2m(4m)= | | 2m(11n)= | | 2m(11n+3)= |